Selection of Material for Marine Environments Using_x000D_ Fuzzy TOPSIS Approach - (:unkn) unknown (My University, 2021)
Material selection for marine environments is an important, difficult, and complex process. For the purpose_x000D_ of decision support, a model was created for the selection of materials for marine environments with the Technique for_x000D_ Order Preference by Similarity to Ideal Solution (TOPSIS) method, which is used for decision-making in fuzzy_x000D_ environments. The decision criteria in the model were determined by an expert, and according to these decision criteria,_x000D_ alternative materials were evaluated with linguistic variables. In the model, there were four main criteria (corrosion_x000D_ resistance, cost, mechanical properties, and workability) and four sub-criteria (yield strength, tensile strength, hardness,_x000D_ and elongation) under the main criteria of mechanical properties. Alternative materials were ranked according to the_x000D_ criteria and alternative material evaluations which were determined by the expert. The software that the created model_x000D_ was applied, developed in the programming language Visual C#. Thanks to the software, decision-makers can obtain_x000D_ different rankings easily by changing the criteria weights and select material for different environments. In the result of_x000D_ the study, applying sensitivity analysis, impact and priority ranking criteria were evaluated._x000D_

Denizel ortamlar için malzeme seçimi önemli, zor ve karmaşık bir süreçtir. Karar destek amacıyla, bulanık_x000D_ ortamlarda karar vermek için kullanılan Bulanık İdeal Çözüm Benzerliği Tercih Sıralaması Tekniği (TOPSIS) yöntemi_x000D_ ile denizel ortamlar için malzeme seçilmesine yönelik bir model oluşturulmuştur. Modelde yer alan karar kriterleri bir_x000D_ uzman tarafından belirlenmiş ve bu karar kriterlerine göre alternatif malzemeler dilsel değişkenler ile değerlendirilmiştir._x000D_ Modelde, dört ana kriter (korozyon direnci, maliyet, mekanik özellik ve işlenebilirlik) ve mekanik özellik ana kriteri_x000D_ altında dört alt kriter (akma mukavemeti, çekme mukavemeti, sertlik ve uzama) bulunmaktadır. Uzman tarafından_x000D_ belirlenen kriter ve alternatif değerlendirmelerine göre alternatif malzemeler sıralanmaktadır. Visual C# programlama_x000D_ dilinde oluşturulan modelin uygulandığı bir yazılım geliştirilmiştir. Yazılım sayesinde karar vericiler kriter ağırlıklarını_x000D_ değiştirerek kolayca farklı sıralamalar elde edebilir ve farklı ortamlar için malzeme seçebilirler. Çalışma sonucunda,_x000D_ oluşturulan modele duyarlılık analizi uygulanarak, kriterlerin etkisi ve öncelik sıralamaları yeniden değerlendirilmiştir.
Bulanık TOPSIS Yaklaşımı ile Denizel Ortamlar için Malzeme Seçimi